Enhancing Scholarly Methanol Poisoning Reports by Utilizing a Standard Diagnostic Tool - Seyed Mostafa Mirakbari (Bulletin of Emergency and Trauma)
ABSTRACT: Methanol poisoning (MP) poses a significant health hazard to public health. It has led to repeated outbreaks of poisoning in our country. However, there is currently no confirmatory test for methanol toxicity, which results in both diagnosis and management, as well as related research, lacking reasonable standards. Definitive confirmation of MP requires the measurement of methanol levels in the blood through gas or liquid chromatography. Unfortunately, such testing is often unavailable, even in prestigious medical centers. The absence of advanced laboratory examinations to confirm methanol toxicity represents a significant limitation in the studies of MPs. The diagnosis of MP in outbreak studies does not appear to have been fully elucidated. The process of patient selection is uncertain and requires clarification. Academic readers learn that the studies rely on patients who were admitted after consuming an alcoholic beverage and subsequently exhibited clinical symptoms commonly associated with MP, such as decreased consciousness, seizures, abdominal pain, blurred vision, and metabolic acidosis. This pattern of approach is consistent with suspected MP but may also be observed in cases of other toxic alcohols. While the combination of these symptoms strongly suggests MP, it does not definitively confirm it. Based on a combination of alleged alcohol consumption history, clinical observations, medical assessments, and metabolic acidosis, MP is assumed to be the primary diagnosis. A breakdown of inclusion criteria, including a confirmatory test, is essential to render the methodology reliable. This paper addresses the deficits in ongoing studies while also introducing recently developed handheld, low-cost and rapid confirmatory methanol tests.Key Words: Diagnosis, Methanol, Poisoning